Pyogenic granuloma of labial mucosa: A misnomer in an anomolous site - Vaiyapuri Ravi; Mathew Jacob; Aandamuthu Sivakumar; Srinivasan Saravanan; Kesavan Priya (Wolters Kluwer Medknow Publications, 2012)
Pyogenic granuloma is tumor-like proliferation to a nonspecific infection. Clinically, pyogenic granuloma presents as sessile or pedunculated exophytic mass with a smooth or lobulated surface which has a tendency to bleed easily. These lesions tend to occur slightly more in females, frequently involving the gingiva of the maxillary region. Histologically, these lesions show an excessive proliferation of vascular type of connective tissue to a nonspecific infection. The most common treatment is surgical excision with eradication of local irritants. This case report describes a pyogenic granuloma on the labial mucosa in a 33-year-old male, discussing the clinical features and histopathologic features that distinguish this lesion from other similar oral mucosa lesions.